Ammonia gas-sensitive material and its preparation method and application
By performing the surface loading of Ag elements and doping of B-position of Mg elements on SmCoO3 material, high-sensitivity ammonia gas-sensitive materials are prepared, which solves the problem of insufficient sensitivity in the detection of low-concentration ammonia in the prior art, and realizes the Excellent response to low concentration ammonia gas and good selectivity and stability.
Patent Information
- Application Number
- CN202411586144.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The prior art lacks sensitivity when detecting low concentrations of ammonia and does not have good adaptability to complex environments, making it difficult to meet the monitoring needs of industrial safety, environmental protection and public health.
The surface loading and modification of Ag elements was carried out on the basis of SmCoO3 material by hydrothermal method, and the B-position doping of Mg elements was used to prepare Xwt% Ag-SmCo1-yMgyO3 ammonia gas-sensitive material, which increased its concentration of ammonia responsiveness.
It achieves excellent response to 2ppm ammonia, has good selectivity and long-term stability, is suitable for portable or low-power devices, and reduces the operating temperature and energy consumption of the sensor.
Smart Images

Figure CN119086661B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to an ammonia gas-sensitive material and a preparation method and application thereof. Background Art
[0002] Ammonia is a common colorless gas with a strong pungent odor, easily soluble in water, and alkaline. Ammonia is widely used in many fields such as chemical industry, agriculture, and pharmaceuticals, especially in the production of fertilizers, refrigeration systems, and wastewater treatment processes, where it has important industrial uses. In addition, ammonia is also used as a diagnostic reagent in the medical industry. However, ammonia is also a potentially toxic substance. High concentrations of ammonia have serious irritating effects on the human respiratory system, eyes, and skin, and long-term exposure may even lead to poisoning. Therefore, real-time monitoring of ammonia leaks is of great significance in the fields of industrial safety, environmental protection, and public health.
[0003] Currently, methods for detecting ammonia include chemical absorption, electrochemical sensors, spectral technology, etc. However, these methods have certain limitations. For example, the chemical absorption detection process is complicated and the operation steps are cumbersome; the spectral detection equipment is expensive and not easy to move; and although the electrochemical sensor has good sensitivity, it is easily affected by factors such as environmental humidity and temperature in practical applications. In addition, these technologies still have room for optimization in terms of response time, detection limit, selectivity, and long-term stability. Based on this, the development of ammonia gas-sensitive materials with high sensitivity, fast response, good selectivity and environmental adaptability has become a research hotspot. Especially in the detection of low-concentration ammonia, gas-sensitive materials are required to maintain reliable performance in complex environments.
[0004] In the prior art, CN111204798A discloses a highly sensitive two-dimensional nano-strontium titanate gas-sensitive material with a low operating temperature, a preparation method and an application thereof. The ultra-thin two-dimensional nano-sheet structure strontium titanate gas-sensitive material prepared using n-butyl titanate and strontium chloride as raw materials can have a good response to 100ppm ammonia at an operating temperature of 20°C, and the sensitivity is above 5. Although the perovskite material strontium titanate prepared in the above patent can achieve a good response to ammonia at room temperature, the concentration of ammonia is 0-10ppm when ammonia leaks. Therefore, the above strontium titanate does not show a good response to low-concentration ammonia. "Preparation of SmCoO3 Nanomaterials and Study on Their Gas Sensing Properties" (Li Qiang et al., Modern Chemical Industry, September 2008, Vol. 28, No. 9) discloses the synthesis of SmCoO3 nanomaterials with a perovskite structure using a citric acid sol-gel method. The nanoparticles are well dispersed, with an average particle size of about 30 nm, and their sensitivity to H2S at 200°C is 20.5. The above SmCoO3 nanomaterials only show a good response to H2S gas, but not to NH3.
[0005] Therefore, developing an ammonia gas-sensitive material with high detection accuracy and suitable for complex environments for detecting low-concentration ammonia has important application value for improving the efficiency and safety of ammonia leakage monitoring. Summary of the Invention
[0006] In view of the above-mentioned prior art, the object of the present invention is to provide an ammonia gas-sensitive material, its preparation method and application. The chemical formula of the ammonia gas-sensitive material is Xwt% Ag-SmCo 1-y Mg y O3, where 0 < X ≤ 20 and 0 < y ≤ 0.5. The present invention is prepared by a hydrothermal method based on the SmCoO3 material, with Ag element used for surface loading and modification, and Mg element used for B-site doping. Among them, through the composite doping modification of noble metal and B-site, the prepared ammonia gas-sensitive material shows excellent sensitivity in detecting ammonia gas, especially good response to low-concentration ammonia. Specifically, at a working temperature of 150 °C, the response value of the ammonia gas-sensitive material prepared by the present invention to 2 ppm ammonia gas is 7.53. At the same time, it shows good selectivity to ammonia and has good long-term stability.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In the first aspect of the present invention, an ammonia gas-sensitive material is provided, and the chemical formula of the ammonia gas-sensitive material is Xwt% Ag-SmCo 1-y Mg y O3, where 0 < X ≤ 20 and 0 < y ≤ 0.5.
[0009] Preferably, the average particle size of the ammonia gas-sensitive material is 55 - 200 nm.
[0010] In the second aspect of the present invention, a preparation method of an ammonia gas-sensitive material is provided, including the following steps:
[0011] (1) Mix samarium nitrate, magnesium nitrate, cobalt nitrate, silver nitrate, citric acid and dilute nitric acid according to the addition amount of (0.01 - 5) mol : (0.01 - 5) mol : (0.01 - 5) mol : (0.01 - 100) g : (20 - 100) g : (5 - 100) mL, and then add them to 10 - 150 mL of deionized water, stir to obtain a mixed solution;
[0012] (2) After carrying out hydrothermal reaction on the mixed solution, cool it to room temperature to obtain a solid product. Wash and dry the solid product to obtain a precursor powder. The hydrothermal reaction temperature is 120 - 200 °C, and the hydrothermal reaction time is 10 - 14 h;
[0013] (3) The precursor powder is calcined at 500-1000°C for 1-5h and then ground to obtain Xwt% Ag-SmCo 1-y Mg y O3 ammonia gas sensitive material.
[0014] Preferably, in step (1), the stirring time is 1.5-2.5 h.
[0015] Preferably, in step (2), the washing treatment is: washing the solid product with deionized water 2-3 times to remove residual impurities therein.
[0016] Preferably, in step (2), the drying temperature is 40-80° C. and the drying time is 2-8 h.
[0017] The third aspect of the present invention provides the use of the ammonia gas-sensitive material in detecting ammonia and / or preparing an ammonia gas-sensitive sensor.
[0018] Preferably, the gas concentration of ammonia is 1-10 ppm.
[0019] Preferably, the ammonia gas-sensitive material is prepared by the following method:
[0020] Ammonia gas-sensitive material, deionized water and pine alcohol are mixed to obtain slurry, the slurry is spin-coated on an alumina substrate to form a gas-sensitive film, and the gas-sensitive film is aged to obtain an ammonia gas-sensitive sensor.
[0021] Further preferably, the added amount ratio of the ammonia gas-sensitive material, deionized water and pinene alcohol is (1-5) g: (3-15) mL: (1-5) mL.
[0022] More preferably, the thickness of the gas sensitive film is 80-200 μm.
[0023] More preferably, the aging temperature is 200-240° C., and the aging time is 10-24 h.
[0024] Beneficial effects of the present invention:
[0025] The present invention adopts hydrothermal method to synthesize ammonia gas-sensitive material Xwt% Ag-SmCo 1-y Mg y O3, the prepared ammonia gas-sensitive material has excellent gas response to low-concentration ammonia. Specifically, at a working temperature of 150°C, the response value of the ammonia gas-sensitive material prepared by the present invention to 2ppm ammonia gas is 7.53, and it shows good selectivity to ammonia. At the same time, the ammonia gas-sensitive material has long-term stability to ammonia gas.
[0026] The present invention uses Ag element to load and modify the surface of SmCoO3 material, uses Mg element to dope the B position of SmCoO3 material, and uses precious metal and B position composite doping modification to make the prepared ammonia gas-sensitive material show excellent sensitivity in detecting ammonia gas, and can effectively distinguish ammonia gas from other interfering gases. At the same time, the ammonia gas-sensitive material prepared by the present invention can reduce the operating temperature of the sensor to 80-220°C, reduce the energy consumption of the sensor, and is suitable for portable or low-power devices.
[0027] The ammonia gas-sensitive material prepared by the present invention is a nano-particle structure, which provides more active sites, effectively improves the gas adsorption and reaction speed, and makes the ammonia gas-sensitive material respond to ammonia gas in only tens of seconds. At the same time, the sol-gel method adopted by the present invention to prepare the ammonia gas-sensitive material has a simple and controllable process, and the material shows good stability in long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : XRD pattern of the ammonia gas-sensitive material based on silver-modified samarium cobalt magnesium oxide prepared in Example 1;
[0029] Figure 2 : SEM image of the ammonia gas-sensitive material based on silver-modified samarium cobalt magnesium oxide prepared in Example 1;
[0030] Figure 3 : A graph showing the relationship between the gas-sensing performance of the ammonia gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 to 2 ppm NH3 gas and temperature;
[0031] Figure 4 : Schematic diagram of the response of the ammonia gas-sensitive material prepared in Example 1 to various gases at 2 ppm;
[0032] Figure 5 : Schematic diagram of the long-term gas-sensitive stability of the ammonia gas-sensitive material prepared in Example 1 to 2 ppm ammonia gas. DETAILED DESCRIPTION
[0033] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0034] Ammonia is a gas with a pungent odor. It is used in many fields such as chemical industry, agriculture, and pharmaceuticals. It is also used as a diagnostic reagent in the medical industry. However, ammonia is a toxic pollutant that can affect the human immune system or inhibit cell growth. In addition, since ammonia is widely used in various production fields, it is inevitable that there will be some leakage during the production process. When ammonia leaks slightly, the concentration of ammonia is 0-10ppm, while the ammonia gas-sensitive materials in the prior art can only detect 100ppm of ammonia and do not show a good response to low concentrations of ammonia gas.
[0035] Based on this, the present invention provides an ammonia gas-sensitive material Xwt% Ag-SmCo 1-y Mg y O3. The ammonia gas-sensitive material is prepared by loading and modifying the surface of SmCoO3 material with Ag element and doping the B-position with Mg element. Among them, through the composite doping modification of precious metals and B-position, the prepared ammonia gas-sensitive material shows excellent sensitivity in detecting ammonia gas, especially showing a good response to low-concentration ammonia. Specifically, its response value to 2ppm ammonia gas is 7.53, and it can effectively distinguish ammonia gas from other interfering gases. At the same time, the ammonia gas-sensitive material prepared by the present invention can reduce the operating temperature of the sensor to 80-220°C, reduce the energy consumption of the sensor, and is suitable for portable or low-power devices.
[0036] In the present invention, the Ag element not only improves the gas-sensing performance of the material through traditional electronic sensitization and chemical sensitization mechanisms, but also interacts with the crystal structure of SmCoO3, enhancing the number and distribution of surface active sites of the material, especially showing higher surface energy during the adsorption process of ammonia molecules. The loading of Ag triggers the electron transfer effect on the surface of the material, significantly improving the reactivity of ammonia molecules at low concentrations, thereby improving the overall gas-sensing performance. In addition, Ag also has good antioxidant properties, which helps to extend the service life and stability of the material.
[0037] The B-site doping of Mg element not only increases the number of oxygen vacancies by adjusting the lattice distortion, but also significantly regulates the conductivity characteristics of the material. Mg doping changes the electron distribution of the material and promotes the dissociation process of ammonia molecules, thereby improving the response speed and sensitivity in low-concentration ammonia detection. In addition, the addition of Mg also enhances the gas-sensitive performance of the material in a wide temperature range, allowing it to maintain a high detection efficiency under low temperature (80-220°C) conditions.
[0038] Through the synergistic effect of Ag and Mg, the material shows excellent detection ability for low-concentration ammonia. Specifically, the response value under 2ppm ammonia is 7.53, and it shows good selectivity, which can effectively distinguish ammonia from other interfering gases. The material also achieves low operating temperature and low energy consumption, which is particularly suitable for portable or low-power gas sensor devices.
[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0040] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.
[0041] Example 1: Ammonia gas sensitive material 10wt% Ag-SmCo 0.5 Mg 0.5 Preparation of O3
[0042] (1) Mix 44.442 g of samarium nitrate, 7.415 g of magnesium nitrate, 9.147 g of cobalt nitrate, 3.75 g of silver nitrate, 50 g of citric acid and 10 mL of dilute nitric acid, add to 50 mL of deionized water, and stir at room temperature for 2 h to ensure full dissolution and form a uniform solution to obtain a mixed solution;
[0043] (2) The mixed solution was transferred to a hydrothermal reaction oven, and the reaction was carried out at 180°C for 12 hours, then cooled to room temperature and filtered to obtain a solid product. The solid product was washed with deionized water for 3 times to remove the remaining impurities, and then dried at 60°C for 6 hours to obtain a precursor powder.
[0044] (3) The precursor powder was calcined at 700 °C for 3 h to enhance its crystallinity and gas sensing properties. The calcined product was ground into fine powder to obtain 10 wt% Ag-SmCo 0.5 Mg 0.5 O3 ammonia gas sensitive material.
[0045] The ammonia gas-sensitive material 10wt% Ag-SmCo prepared in this embodiment 0.5 Mg 0.5 O3 was used for structural characterization, and the results were as follows Figure 1-Figure 2 shown.
[0046] Depend on Figure 1 It can be seen that the crystallization peaks correspond to the (200), (020) and (220) crystal phases of SmCoO3 (NO.25-1071), and the (101) characteristic peak of the Mg element and the (111) characteristic peak of the Ag element can be clearly seen, which shows that the Ag element and the Mg element exist in this material.
[0047] Depend on Figure 2 It can be seen that the ammonia gas-sensitive material presents a typical nanoparticle structure, and the specific surface area of the material is 13.8 m 2 / g and the pore diameter is 30-80 nm. It can be seen that the ammonia gas-sensitive material prepared by the present invention has a large specific surface area and large pores, and the reaction sites and transmission channels of the gas molecules in the ammonia gas-sensitive material are more.
[0048] Example 2: Ammonia gas-sensitive material 5 wt% Ag-SmCo 0.3 Mg 0.7 Preparation of O3
[0049] (1) Mix 44.442 g of samarium nitrate, 10.381 g of magnesium nitrate, 5.488 g of cobalt nitrate, 1.81 g of silver nitrate, 60 g of citric acid and 20 mL of dilute nitric acid, add to 60 mL of deionized water, and stir at room temperature for 1.5 h to ensure full dissolution and form a uniform solution to obtain a mixed solution;
[0050] (2) The mixed solution was transferred to a hydrothermal reaction oven, and the reaction was carried out at 120°C for 10 hours, then cooled to room temperature, filtered, and a solid product was obtained. The solid product was washed with deionized water for 3 times to remove the remaining impurities, and then dried at 40°C for 8 hours to obtain a precursor powder.
[0051] (3) The precursor powder was calcined at 700 °C for 5 h to enhance its crystallinity and gas sensing properties. The calcined product was ground into fine powder to obtain 5 wt% Ag-SmCo 0.3 Mg 0.7 O3 ammonia gas sensitive material.
[0052] Example 3: Ammonia gas sensitive material 15 wt% Ag-SmCo 0.7 Mg 0.3 Preparation of O3
[0053] (1) 44.442 g of samarium nitrate, 4.449 g of magnesium nitrate, 12.805 g of cobalt nitrate, 5.84 g of silver nitrate, 55 g of citric acid and 15 mL of dilute nitric acid were mixed, and then added into 55 mL of deionized water, and stirred at room temperature for 2.5 h to ensure that the mixture was fully dissolved and a uniform solution was formed, to obtain a mixed solution;
[0054] (2) The mixed solution was transferred to a hydrothermal reaction oven, and the hydrothermal reaction was carried out at 200°C for 14 hours, then cooled to room temperature, filtered, and a solid product was obtained. The solid product was washed with deionized water for 3 times to remove the remaining impurities, and then dried at 80°C for 2 hours to obtain a precursor powder.
[0055] (3) The precursor powder was calcined at 1000 °C for 1 h to enhance its crystallinity and gas sensing properties. The calcined product was ground into fine powder to obtain 15 wt% Ag-SmCo 0.7 Mg 0.3 O3 gas sensitive material.
[0056] Example 4: Preparation of ammonia gas sensor
[0057] The ammonia gas-sensitive material prepared in Example 1, deionized water and pinene alcohol were mixed in an addition ratio of 1 g: 3 mL: 1 mL to obtain a slurry, which was spin-coated on the surface of an aluminum oxide ceramic tube at a rotation speed of 600 rpm to form a 208 μm gas-sensitive film, and the gas-sensitive film was placed in air and aged at 220° C. for 20 h to obtain an ammonia gas-sensitive sensor.
[0058] Comparative Example 1: Preparation of ammonia gas-sensitive material SmCoO3
[0059] The difference between this comparative example and Example 1 is that in step (1), no silver nitrate and magnesium nitrate are added, and the obtained gas-sensitive material is SmCoO3.
[0060] Comparative Example 2: Ammonia gas-sensitive material SmCo 0.5 Mg 0.5 Preparation of O3
[0061] The difference between this comparative example and Example 1 is that in step (1), no silver nitrate is added, and the gas-sensitive material prepared is SmCo 0.5 Mg0.5O3.
[0062] Comparative Example 3: Preparation of 10 wt% Ag-SmCoO3 ammonia gas-sensitive material
[0063] The difference between this comparative example and Example 1 is that in step (1), magnesium nitrate is not added, and the gas-sensitive material prepared is 10 wt% Ag-SmCoO3.
[0064] Test example: Gas sensing performance test
[0065] The ammonia gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 were coated on the sensing film, and their gas-sensitive responses (Rg / Ra) to 2ppm NH3, CO and other gases were tested respectively. The results are as follows: Figure 3-Figure 4 As shown. Among them, Ra is the resistance of the sensor in the air, and Rg is the resistance of the gas being measured. The experimental environment is: RH is 20%, and the ambient temperature is 20℃.
[0066] Depend on Figure 3It can be seen that the optimal working temperature of the ammonia gas-sensitive material prepared by the present invention is 150°C. At a working temperature of 150°C, the response value of the ammonia gas-sensitive material prepared by the present invention to 2 ppm NH3 gas is 7.53, the response value of the ammonia gas-sensitive material SmCoO3 prepared in Comparative Example 1 to 2 ppm NH3 gas is 1.98, and the ammonia gas-sensitive material SmCoO3 prepared by only using Mg element to dope the SmCoO3 material at the B position in Comparative Example 2 is 1.98. 0.5 Mg 0.5 The response value of SmCoO3 to 2 ppm NH3 gas is 2.78. In Comparative Example 3, only Ag element was used to load and modify the surface of SmCoO3 material, and the response value of the prepared ammonia gas-sensitive material 10 wt% Ag-SmCoO3 to 2 ppm NH3 gas was 5.81. It can be seen that the loading and modification of precious metals on the surface of SmCoO3 material and the doping of Mg element at the B position have a synergistic effect in improving the response value of the ammonia gas-sensitive material to NH3 gas.
[0067] Depend on Figure 4 It can be seen that when exposed to multiple gases, the ammonia gas-sensitive material 10 wt% Ag-SmCo prepared by the present invention 0.5 Mg 0.5 The selectivity of O3 to 2 ppm NH3 gas is significantly higher than that to gases including CO, CO2, etc., which shows that the gas-sensitive material prepared by the present invention has good selectivity to ammonia gas.
[0068] Long-term stability is another important characteristic of gas-sensitive materials. The higher the long-term stability, the longer the replacement cycle of the gas-sensitive material, and the greater the economic and energy advantages. Figure 5 The ammonia gas sensitive material 10 wt% Ag-SmCo prepared by the present invention is shown 0.5 Mg 0.5 The long-term stability of O3 to 2 ppm NH3 gas. It can be seen that within one month, the ammonia gas-sensitive material 10 wt% Ag-SmCo 0.5 Mg 0.5 The response value change rate of O3 to 2 ppm NH3 gas is within 2%, indicating that the material has extremely high long-term stability in gas sensing.
[0069] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An ammonia gas-sensitive material, characterized in that: The chemical formula of the ammonia gas-sensitive material is Xwt% Ag-SmCo 1- y Mg y O3, where 0 < X ≤ 20, 0 < y ≤ 0.5, and the average particle size of the ammonia gas-sensitive material is 55 - 200 nm; The ammonia gas-sensitive material is prepared by the following method: (1) Samarium nitrate, magnesium nitrate, cobalt nitrate, silver nitrate, citric acid and dilute nitric acid are mixed in the following amounts: (0.01-5) mol: (0.01-5) mol: (0.01-5) mol: (0.01-100) g: (20-100) g: (5-100) mL, and then added to 10-150 mL of deionized water, and stirred to obtain a mixed solution; (2) After the mixed solution is subjected to a hydrothermal reaction, it is cooled to room temperature to obtain a solid product, and the solid product is washed and dried to obtain a precursor powder. The hydrothermal reaction temperature is 120-200°C and the hydrothermal reaction time is 10-14h; (3) The precursor powder is calcined at 500-1000°C for 1-5h and then ground to obtain Xwt% Ag-SmCo 1-y Mg y O3 ammonia gas sensitive material.
2. The ammonia gas-sensitive material according to claim 1, characterized in that: In step (1), the stirring time is 1.5-2.5h.
3. The ammonia gas-sensitive material according to claim 1, characterized in that: In step (2), the drying temperature is 40-80°C and the drying time is 2-8h.
4. Use of the ammonia gas-sensitive material according to any one of claims 1 to 3 in detecting ammonia and / or preparing an ammonia gas-sensitive sensor.
5. The use according to claim 4, characterized in that The gas concentration of the ammonia gas is 1-10 ppm.
6. The use according to claim 4, characterized in that The ammonia gas sensor is prepared by the following method: The ammonia gas-sensitive material according to any one of claims 1 to 3, deionized water and pine alcohol are mixed to obtain a slurry, the slurry is spin-coated on an alumina substrate to form a gas-sensitive film, and the gas-sensitive film is aged to obtain an ammonia gas-sensitive sensor.
7. The use according to claim 6, characterized in that The added amount ratio of the ammonia gas-sensitive material, deionized water and pinene alcohol is (1-5) g: (3-15) mL: (1-5) mL; the aging temperature is 200-240° C., and the aging time is 10-24 h.